2014
DOI: 10.1073/pnas.1320192111
|View full text |Cite
|
Sign up to set email alerts
|

Aβ-induced Golgi fragmentation in Alzheimer’s disease enhances Aβ production

Abstract: Golgi fragmentation occurs in neurons of patients with Alzheimer's disease (AD), but the underlying molecular mechanism causing the defects and the subsequent effects on disease development remain unknown. In this study, we examined the Golgi structure in APPswe/PS1ΔE9 transgenic mouse and tissue culture models. Our results show that accumulation of amyloid beta peptides (Aβ) leads to Golgi fragmentation. Further biochemistry and cell biology studies revealed that Golgi fragmentation in AD is caused by phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
189
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(198 citation statements)
references
References 47 publications
8
189
0
1
Order By: Relevance
“…Nevertheless, the demonstration that Golgi dysfunction causes neuronal loss in vivo, combined with the observation that neuronal loss and ataxia worsen with age upon loss of GM130, indicates that this process could, in principle, result in or at least contribute to the neurodegeneration that occurs in human disease. In support of this possibility, it has been shown that α-synuclein can perturb ER-to-Golgi traffic in Parkinson's disease models (49), and that the Aβ-fragment of APP that causes Alzheimer's disease, and the pathogenic form of ataxin-2 that causes SCA2, both disrupt Golgi organization (19,50). Hence, Golgi dysfunction and defective secretory trafficking, which could be attributable to a number of primary causes, may represent a significant pathogenic mechanism of neurodegenerative disease in humans.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the demonstration that Golgi dysfunction causes neuronal loss in vivo, combined with the observation that neuronal loss and ataxia worsen with age upon loss of GM130, indicates that this process could, in principle, result in or at least contribute to the neurodegeneration that occurs in human disease. In support of this possibility, it has been shown that α-synuclein can perturb ER-to-Golgi traffic in Parkinson's disease models (49), and that the Aβ-fragment of APP that causes Alzheimer's disease, and the pathogenic form of ataxin-2 that causes SCA2, both disrupt Golgi organization (19,50). Hence, Golgi dysfunction and defective secretory trafficking, which could be attributable to a number of primary causes, may represent a significant pathogenic mechanism of neurodegenerative disease in humans.…”
Section: Discussionmentioning
confidence: 97%
“…In the pathogenic chain of AD, the further fragmentation of GA induced by Aβ peptide overproduction [29] may reasonably affect dendritic protein trafficking, which is essentialfor dendritic remodeling and arbor stability, since microtubules are closely associated with Golgi outpost and trafficking of vesicles and proteins towards the terminal dendritic branches and spines [30]. At the same time the Aβ peptide which is accumulated in multivesicular bodies [31], in association with mitochondrial dysfunction [32] may induce disruption of the synapses [31], a fact which is closely related with the cognitive decline in AD.…”
mentioning
confidence: 99%
“…This result indicates that the unusual features observed for CnGRASP are not a consequence of uncompensated electrical charges along its amino acid sequence. We also observed that CnGRASP mutants intended to mimic site-directed phosphorylation in the SPR domain do not show disorder-to-order transitions, even though phosphorylation has proven important for breaking GRASP homo-dimerization and contributing to Golgi structural dynamics [52,53,57,60].…”
Section: Discussionmentioning
confidence: 76%
“…It was shown a correlation between β-amyloid peptides accumulation in the extracellular environment and the Golgi fragmentation caused by GRASP phosphorylation in Alzheimer disease [60]. In this process, the GRASP phosphorylation inhibition recovers the healthy Golgi phenotype and leads to a significant decrease of the β-amyloid peptides secretion, suggesting that the Golgi and GRASPs could be interesting targets in the pharmacologic strategies against Alzheimer disease [60].…”
mentioning
confidence: 99%
See 1 more Smart Citation